2023
DOI: 10.1108/nfs-08-2022-0267
|View full text |Cite
|
Sign up to set email alerts
|

Individual determinants of Mediterranean diet adherence among urban Lebanese adult residents

Abstract: Purpose Many studies revealed positive health impacts of the Mediterranean diet (MedDiet), especially on metabolic disorders. Conversely, in Lebanon, recent information about determinants of adherence to the MedDiet are limited. This study aimed to examine the individual determinants of MedDiet adherence among adults in Lebanon. Design/methodology/approach A cross-sectional study was carried out during July 2021 among a convenient sample of 326 Lebanese adults. Data from participants were collected via an on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…It was found that there was no significant difference between MEDAS scores according to gender (p>0.05). (Malakieh et al, 2022(Malakieh et al, , pp.1033(Malakieh et al, -1044found the mean MEDAS score was 7.59 ± 2.22 in their study on 326 Lebanese adults, which reflects acceptable adherence. In the study conducted on 1,197 adult volunteers, the MEDAS score was determined as 6.68±2.49.…”
Section: Discussionmentioning
confidence: 86%
“…It was found that there was no significant difference between MEDAS scores according to gender (p>0.05). (Malakieh et al, 2022(Malakieh et al, , pp.1033(Malakieh et al, -1044found the mean MEDAS score was 7.59 ± 2.22 in their study on 326 Lebanese adults, which reflects acceptable adherence. In the study conducted on 1,197 adult volunteers, the MEDAS score was determined as 6.68±2.49.…”
Section: Discussionmentioning
confidence: 86%